ANALYSIS OF STUDENTS’ MULTICULTURAL BACKGROUNDS ON DRAMA PERFORMANCE IN HIGHER EDUCATION - Eripuddin; Pipit Rahayu; Nuri Pratama, (JEE (Journal of English Education), 2024)
This study explores how multicultural backgrounds influence drama performances among fifth semester English Department students at University Pasir Pengaraian. This study uses the qualitative methods. The instrumentation of this study such as questionnaires and performance documentation. The research shows how multicultural backgrounds shape students' engagement and perspectives in drama. The key findings indicate that cultural research enriches drama scripts, multicultural experiences enhance character development, and participation in diverse drama performances reduces prejudice and fosters empathy. Inclusive pedagogy and effective techniques ensure equitable participation, promoting inclusion, solidarity, and respect for diversity. Overall, the study highlights the positive influence of multicultural education on students' cultural awareness and attitudes, emphasizing the importance of integrating diverse perspectives to enrich artistic expression and foster an inclusive learning environment.